Pengetahuan kepala rumah tangga tentang Third-Hand Smoke (THS) dan keluhan pernapasan pada anak - Gst. Kade Adi Widyas Pranata; Anak Agung Istri Wulan Krisnandari Dalem (Holistik Jurnal Kesehatan, 2021)
Householder knowledge regarding third-hand tobacco smoke exposure and respiratory complaints in children Background: Third-hand smoke (THS) is very dangerous, especially for children because of its content, properties, and the ability to last a long time on the surface of objects for months. Parents or families do not seem to care and know this hidden danger since they think as long as they do not smoke in front of their children, it means there is no problem.Purpose: To identify the householder knowledge regarding third-hand tobacco smoke exposure and respiratory complaints in childrenMethod: This descriptive survey research with a cross-sectional approach was carried from August to November 2020 with householders of active smokers. The sampling technique was cluster sampling with a sample size of 561 respondents. The research instrument used the "Parent and Family Behavior Questionnaire against THS". Descriptive data analysis using SPSS 20 for Windows.Results: Most of householders with active smokers had poor knowledge of THS by 451 respondents (80.4%), respiratory complaints in children were reported in 475 (84.7%) cases and the correlation between knowledge of householders about THS and respiratory complaints in children obtained p-value 0.000Conclusion: Most of householders with active smokers had poor level of knowledge about THS and a significant relationship with respiratory complaints in childrenKeywords: Knowledge; Householder; Third-Hand Smoke; Respiratory Complaints; ChildrenPendahuluan: Third-hand smoke (THS) sangatlah berbahaya terutama bagi anak-anak karena kandungan, sifat dan kemampuan bertahan lama pada permukaan benda hingga berbulan-bulan. Orang tua ataupun keluarga tampaknya tidak cukup peduli dan mengetahui bahaya tersembunyi ini sejak mereka menganggap selama tidak merokok di depan anak, itu berarti tidak ada masalah.Tujuan: Untuk mengidentifikasi pengetahuan kepala rumah tangga tentang paparan THS dan keluhan pernapasan pada anak-anakMetode: Penelitian survei deskriptif dengan pendekatan cross sectional ini dilakukan pada bulan Agustus hingga November 2020 terhadap kepala rumah tangga yang merupakan perokok aktif. Teknik pengambilan sampel adalah cluster sampling dengan jumlah sampel 561 responden. Instrumen penelitian menggunakan “Kuesioner Perilaku Orang Tua dan Keluarga Terhadap THS”. Analisis data deskriptif menggunakan SPSS 20 for Windows.Hasil: Sebagian besar kepala rumah tangga perokok aktif memiliki pengetahuan buruk tentang THS sebesar 451 responden (80.4%), keluhan pernapasan pada anak dilaporkan terdapat 475 (84.7%) kasus dan korelasi antara pengetahuan kepala rumah tangga tentang THS dengan keluhan pernapasan pada anak diperoleh p-value 0.000Simpulan: Sebagian besar kepala rumah tangga yang merupakan perokok aktif memiliki tingkat pengetahuan buruk tentang THS dan memiliki hubungan yang signifikan dengan keluhan pernapasan pada anak